Aplikasi Tiktok Sebagai Media Representasi Diri Pada Remaja di SMPN 2 Alalak Kabupaten Barito Kuala - Anggraeni Aticka; Khairussalam (Prodi Sosiologi FISIP ULM, 2023)
Mobile phones are part of everyday human life, especially if there is the Tiktok application in it which can allow humans to connect with millions of people in various parts of the world. This study aims to determine the self-representation of adolescents at SMP Negeri 2 Alalak, Batola Kuala Regency using the tiktok application as a medium of self-representation. This research uses a qualitative approach. The data in this study were obtained by observing, interviewing and documenting. The data analysis technique used was adapted from Miles and Huberman (2014) covering 4 stages, namely data collection, data reduction, data presentation and drawing conclusions. The results showed that there were several factors resulting from the use of the tiktok application including imitation/psychological factors, suggestion, identification and sympathy. On the imitation/psychological factor, adolescents will imitate public figures in society. In the suggestion factor, teenagers are affected by the existence of advertisements. The identification factor is driven by the desire of adolescents to show their existence in society. Teenagers who are influenced by sympathy because they are inspired by their idols. The results of using Tiktok are adding insight and knowledge to teenagers, increasing creativity and as a medium of propaganda. However, the impact of using Tiktok is reduced study time, detrimental to health and reduced self-representation in the environment. Adolescents' self-representation in using Tiktok is more influenced by several factors, namely imitation/psychology, suggestion and sympathy.